Seropositivity of Epstein-Barr virus in Eastern Anatolian Region of Turkey - Ozkan, A; Kilic, SS; Kalkan, A; Ozden, M; Demirdag, K; Ozdarendeli, A (Allergy Immunol Soc Thailand, 2003)
In the present study, we have investigated the seropositivity of Epstein-Barr virus (EBV) and the epidemiological factors affecting this seropositivity. A total of 540 subjects living in central Elazig Province and its surroundings were enrolled in the study. IgG antibodies against capsid antigen of EBV (anti-VCA IgG) were determined by ELISA. Seropositivity was found to be 99.4%. There was a significant relationship between increased anti-VCA IgG levels and age, living in crowded families, exposure in public places and low income (p < 0.05). However, no significant alterations in serum anti-VCA IgG antibody were observed in terms of gender, blood transfusion and educational status (p > 0.05). In conclusion, we have demonstrated the commonly presence of EBV infections in the public and contamination with the infection at early stages of life in the Elazig region. An overpopulated family environment, low income status and living in shared accommodation facilities play important roles in acquiring EBV infection.
Keywords: Prevalence; Infections; Children; Antibody